Las mujeres : entre el sacrificio y la negociación (2013)
ABSTRACT: An idea commonly held is that social transformations automatically translate into subjective ones. However, this is not the case, and particularly when it comes to the social, political and economic rights of women. There are subjective obstacles that prevent the emergence of adequate positions that allow women to exercise ownership and socially recognized rights. Investigating this issue involves looking at the relation between power and subjectivity, both revealing how inaccurate it is to assume that power manifests exclusively in the public sphere.